Novel Analgesics with Peripheral Targets - Ciotu, Cosmin I. (Neurotherapeutics, 2020)
A limited number of peripheral targets generate pain. Inflammatory mediators can sensitize these. The review addresses targets acting exclusively or predominantly on sensory neurons, mediators involved in inflammation targeting sensory neurons, and mediators involved in a more general inflammatory process, of which an analgesic effect secondary to an anti-inflammatory effect can be expected. Different approaches to address these systems are discussed, including scavenging proinflammatory mediators, applying anti-inflammatory mediators, and inhibiting proinflammatory or facilitating anti-inflammatory receptors. New approaches are contrasted to established ones; the current stage of progress is mentioned, in particular considering whether there is data from a molecular and cellular level, from animals, or from human trials, including an early stage after a market release. An overview of publication activity is presented, considering a IuPhar/BPS-curated list of targets with restriction to pain-related publications, which was also used to identify topics. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13311-020-00937-z.) contains supplementary material, which is available to authorized users.